2014
DOI: 10.1073/pnas.1315588111
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic genetic array screen identifies PP2A as a therapeutic target in Mad2-overexpressing tumors

Abstract: Significance The spindle checkpoint is required for proper chromosome segregation. Mitotic arrest deficiency 2 (Mad2), a component of the spindle checkpoint, is overexpressed in many cancer cells. This phenotype can be used to specifically kill Mad2-overexpressing tumor cells. Because the spindle checkpoint pathway is highly conserved between yeast and humans, we performed a screen to identify mutants in which Mad2 overexpression kills yeast cells. The screen revealed that Mad2 overexpression induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…Mad2 overexpression is a hallmark in many cancers, and PP2A inhibition has been suggested as a therapeutic means of targeting Mad2-overexpressing tumor cells. 16 Western blotting demonstrated that LB100 exhibited a concentration-dependent decrease in Mad2 expression in 143B cells (Fig. 2C).…”
Section: Lb100 Sensitizes Osteosarcoma Cells To the Cytotoxic Effectsmentioning
confidence: 93%
“…Mad2 overexpression is a hallmark in many cancers, and PP2A inhibition has been suggested as a therapeutic means of targeting Mad2-overexpressing tumor cells. 16 Western blotting demonstrated that LB100 exhibited a concentration-dependent decrease in Mad2 expression in 143B cells (Fig. 2C).…”
Section: Lb100 Sensitizes Osteosarcoma Cells To the Cytotoxic Effectsmentioning
confidence: 93%
“…Although SDL has been used to identify protein targets of enzymes (82,100,101) and to identify specific subsets of genes within chromosome segregation mutants (29), it is underused to uncover genetic contexts that could selectively target cancer cells with elevated levels of a specific gene (26,27,102). SDL screens therefore represent a powerful approach for fast and easy identification of candidate chemotherapeutic drug targets within the context of dCIN gene overexpression that could enable targeted elimination of these cells.…”
Section: Sdl Screens As a Platform To Identify Therapeutic Targets Inmentioning
confidence: 99%
“…Most SL approaches focus on exploiting specific somatic mutations or deletions in cancer driver genes; however, there are just as many amplified regions as deleted regions in cancer genomes (17). Thus, we propose using synthetic dosage lethality (SDL), which is SL with an amplified and/or overexpressed gene, as an approach to selectively target tumors that overexpress dCIN genes (26,27). SDL occurs when the overexpression of a gene is not lethal in a wild-type background but in conjunction with a second site nonlethal mutation causes lethality (28)(29)(30).…”
mentioning
confidence: 99%
“…Our results showed that co-transfection of a MAD2 expression plasmid 10 (that is RNAi-resistant in our system) can rescue the phosphorylation of histone H3S28 in MAD2-silenced HeLa cells. The recovery in the level of histone H3 phosphorylation was comparable to the control cells (Fig.…”
Section: Mad2 Regulates Aurora B-mediated Mitotic Phosphorylation Of mentioning
confidence: 64%